ASSESSMENT OF THE STATUS OF PRIVATE AND NON-GOVERNMENTAL PHARMACEUTICALS SUPPLY WAREHOUSES IN GAZA STRIP, PALESTINE. - Tabash, Mohammed; Abuqamar, Mazer (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: Storage of medicine is one of the most important stages in the pharmaceuticals and medical preparations management, which influences the quality and the effectiveness of these products. The study was conducted to assess the storage system of the drugs, medical disposables and their management in the private and local NGOs medical warehouses in Gaza Strip. Methods: A cross-sectional study using interviewing questionnaire and checklist was carried out at (16) local NGOs including 33 employees and (29) private warehouses including 57 employees. Results: The quality of construction of private and local warehouses were enough satisfied (80%), while stock management and quality control were in a need to improvement (44.5%), in which the quality of stock control and conditions of local NGOs were higher than private warehouses. Inadequate training courses were given in store related work. The majority of warehouses did not have practical guidelines and written procedures for dealing with storage procedure; also, there is inadequate safety and security system. About 37% of them kept controlled drugs in a separate storage space designated for this purpose. More than half of warehouses always quarantined medical supplies until the quality is checked. 60% of warehouses used first expire first out dispensing policy for medical supplies. 56% of the warehouses measure temperature, while not all warehouses measured humidity. Conclusion: Warehouses need to pay attention to the commodity management cycle and to ensure the availability of safety measurements. Provision of training to employees dealing with the storage process is essential accompanied by monitoring and supervision.